COMPARATIVE ANALYSIS OF ONLINE AND OFFLINE SHOPPING AT WARS.LAB STORE PURCHASE - Warren Tengker; Willem J. F. A. Tumbuan; Maria V. J. Tielung (Universitas Sam Ratulangi, 2023)
The fundamental issue which arises right now in front of a consumer when he/she embarks on buying something is which modes of shopping they should choose to satisfy themselves. There are both online and offline shops available to fulfil their purchase interest. This study tries to answer more about the comparative selling modes, therefore, this study tries to identify differences in online and offline shopping at Wars.Lab store. The research method that been used is quantitative approach. The sample in this research is consisting of 100 respondents. The analysis method that been used is independent samples t-test used to compare two groups whose means are not dependent on one another. From all the results above, it has been analyzed that there are no significant differences between online and offline shopping based on product price and promotion. Perception of every person may be different, but in this case customer preferences on product factors have the same perception, because things that have given or support product to customers have the same. Keywords: online and offline store, comparative analysis, shopping product